2008
DOI: 10.1074/mcp.m700216-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

ANIBAL, Stable Isotope-based Quantitative Proteomics by Aniline and Benzoic Acid Labeling of Amino and Carboxylic Groups

Abstract: Identification and relative quantification of hundreds to thousands of proteins within complex biological samples have become realistic with the emergence of stable isotope labeling in combination with high throughput mass spectrometry. However, all current chemical approaches target a single amino acid functionality (most often lysine or cysteine) despite the fact that addressing two or more amino acid side chains would drastically increase quantifiable information as shown by in silico analysis in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…The Hystar program (Bruker) was used to define the HPLC and mass spectrometry methods that were used to develop the solvent gradient and MS tune method and integrate the instruments used (8). Other MS and LC systems can be used with appropriate modifications to these protocols (911).…”
Section: Methodsmentioning
confidence: 99%
“…The Hystar program (Bruker) was used to define the HPLC and mass spectrometry methods that were used to develop the solvent gradient and MS tune method and integrate the instruments used (8). Other MS and LC systems can be used with appropriate modifications to these protocols (911).…”
Section: Methodsmentioning
confidence: 99%
“…These latter observations raise important questions regarding the potential pleiotropic effects of the 5-LO pathway on components of the metabolic syndrome. For example, recent studies in humans and mice have demonstrated that various pharmacological modifiers of the 5-LO pathway decrease inflammatory biomarkers and aortic lesion formation, respectively, [7][8][9], raising the possibility of developing 5-LO pathway inhibitors for the treatment of CVD. Our results suggest that it would be important for such therapeutic strategies to carefully consider potentially undesirable metabolic effects as well despite the pro-atherogenic role that 5-LO pathway genes appear to play in humans.…”
Section: H Allayeementioning
confidence: 99%
“…Our Nutrigenomics and Nutrigenetics research will be exemplified with own tool developments [5][6][7] and application areas like nutritional modulation of immunity, digestive health [8,9] diabetes and obesity as well as bioavailability and bioefficacy of health-beneficial ingredients [10,11].…”
Section: Kussmannmentioning
confidence: 99%
“…The EDC-based coupling reaction has been well developed and widely used. 2123 The reaction can be performed in aqueous solution under relatively mild conditions around neutral pH which prevents DNA degradation. The carboxylic acid group can react with EDC to form an o -acylisourea ester intermediate that can then be attacked by a primary amine (Scheme 1).…”
mentioning
confidence: 99%